2013
DOI: 10.1097/gme.0b013e318259eaf3
|View full text |Cite
|
Sign up to set email alerts
|

Baseline hysteroscopic assessment of endometrium in asymptomatic postmenopausal women with estrogen receptor–positive breast cancer

Abstract: Asymptomatic postmenopausal women with ER-positive breast cancer have a very high prevalence of baseline subclinical endometrial abnormalities. Therefore, endometrial screening before tamoxifen treatment may be useful in all of these patients, and we believe that it should be performed by hysteroscopy in patients at high risk (obese and older women).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In a recent study, the baseline hysteroscopic assessment revealed an incidence of 31.3% of overall endometrial morbidity in asymptomatic postmenopausal ERα+ breast cancer patients (9). For patients who have endometrial conditions such as hyperplasia without atypia prior to tamoxifen treatment, the rate of progression to more advanced stage endometrial lesions is almost 50% after 24 months of tamoxifen administration (10).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the baseline hysteroscopic assessment revealed an incidence of 31.3% of overall endometrial morbidity in asymptomatic postmenopausal ERα+ breast cancer patients (9). For patients who have endometrial conditions such as hyperplasia without atypia prior to tamoxifen treatment, the rate of progression to more advanced stage endometrial lesions is almost 50% after 24 months of tamoxifen administration (10).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to spread among oncologists and gynecologists the value of hysteroscopy, as the main obstacle that we encounter is the lack of information for patients about this possibility and referring patients for routine blind curettage. Therefore, patients are not informed about the significant value of hysteroscopy over TVS or curettage in tamoxifen-treated patients [1–5]. …”
Section: Discussionmentioning
confidence: 99%
“…These patients are carefully followed during tamoxifen treatment by their oncologists, but they rarely have their baseline endometrial assessment performed by their gynecologist. A recent Spanish study proved the value of hysteroscopic assessment prior to treatment even in asymptomatic postmenopausal women with ER-positive receptors [1]. These findings are crucially important in the case of obese, older women whose risk of endometrial pathology is primarily greater than the population risk.…”
Section: Introductionmentioning
confidence: 99%